Effect of Lead Exposure on AST Enzyme in Individuals Who Smoke - Agnes Felicia Lubis; Lidwina Septie Christyawardani; Lusia Sudarmi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Cigarettes are one of the consumer products that are popular with the public. The composition of cigarettes includes tobacco, cloves, and other additives. One of the additives that is often used is lead. Lead can also be carcinogenic, meaning it can cause cancer. Exposure to lead in active smokers can cause various health hazards, especially those related to liver damage. Increased levels of lead in the body of smokers can cause liver cell damage, which can be reflected in increased levels of the enzyme AST (aspartate aminotransferase) in the blood. This study aims to see the effect of this heavy metal on the levels of the Aspartate Aminotransferase Enzyme in Individuals Who Smoke. This research method uses a descriptive introduction with a simple random sampling approach. The subjects of this study consisted of 10 people who were drivers with an average age of 25 years who had been smoking for 5-8 years. Blood lead levels were measured using the APHA method, and AST enzyme levels were measured using the IFCC method. The results showed that there was no relationship between blood lead levels and AST levels in smokers and blood lead levels (significance: 0.066). The average lead level in the blood of active smokers is still below the threshold, which is 34.1437 µg/L (100–250 µg/L). Suggestions for further research are to conduct research to see the relationship between lead levels and Alanine Aminotransferase (ALT) enzyme levels in online motorcycle taxi drivers and cleaners in the city of Palembang.